Penerapan Technology Acceptance Model dalam Meningkatkan Minat Menggunakan Kembali M-Banking Livin by Mandiri - Salsa Dea Safira; Diah Ernawati; Muhammad Iqbal (Politeknik Negeri Batam, 2023)
The development of the Technology Acceptance Model in encouraging people to use technology continues to develop. Mobile banking as one of the most popular technologies today is still not used optimally by customers. Various factors were identified to influence the decision to use mobile banking, such as: perceived usefulness, perceived convenience, trust, convenience, satisfaction, and social influence. Regression analysis with the Ordinary Least Squared (OLS) approach is used to identify the priority factors in driving customer decisions to use mobile banking. The results obtained indicate that the higher the perception of usefulness, trust, convenience, satisfaction, and social influence on mobile banking, the higher the decision to use it. Conversely, the lower the perception of usefulness, trust, convenience, satisfaction, and social influence on mobile banking, the decision to use it will also decrease. Meanwhile, the level of perceived convenience does not affect the decision to use mobile banking.